IMPACT OF COLOR ON OUR - Sabyasachi, Rana (International Journal of Research -GRANTHAALAYAH, 2014)
There are many colors in our world. Think of how bland and unexciting it would be without color. Colors light up our surroundings, and inspire us to be creative. Life would have been terribly drab if colors did not exist. I cannot imagine a world where there was a total absence of color. It is enough for us to look at the dawn after the darkness of night to know the difference. Landscapes and seascapes take life from the different shades of greens and blues, the colors of the birds' feathers, the different colors of fish, and the multicolored flowers.